The presence of a 5′-abasic lesion enhances discrimination of single nucleotide polymorphisms while inducing an isothermal ligase chain reaction. Issue 14 (21st June 2016) - Kausar, Abu; Osman, Eiman A.; Gadzikwa, Tendai; Gibbs-Davis, Julianne M.
Abstract : Lesion-induced DNA amplification (LIDA) has been employed in the detection of single nucleotide polymorphisms (SNPs). Abstract : Lesion-induced DNA amplification (LIDA) has been employed in the detection of single nucleotide polymorphisms (SNPs). Due to the presence of the proximal abasic lesion, T4 DNA ligase exhibits greater intolerance to basepair mismatches when compared with mismatch ligation in the absence of the abasic lesion. Moreover the presence of the abasic group also results in an isothermal ligase chain reaction enabling SNP detection with great discrimination and sensitivity. Specifically, at forty minutes, the ratio of amplified product from the matched and mismatched initiated reactions are 7–12 depending on the mismatch. The ease of implementation of our method is demonstrated by real-time analysis of DNA amplification using a fluorescent plate reader.